2021
DOI: 10.1021/jacs.1c04069
|View full text |Cite
|
Sign up to set email alerts
|

C–H Activation by RuCo3O4 Oxo Cubanes: Effects of Oxyl Radical Character and Metal–Metal Cooperativity

Abstract: High-valent multimetallic-oxo/oxyl species have been implicated as intermediates in oxidative catalysis involving proton-coupled electron transfer (PCET) reactions, but the reactive nature of these oxo species has hindered the development of an in-depth understanding of their mechanisms and multimetallic character. The mechanism of C–H oxidation by previously reported RuCo3O4 cubane complexes bearing a terminal RuV–oxo ligand, with significant oxyl radical character, was investigated. The rate-determining step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 67 publications
(122 reference statements)
5
8
0
Order By: Relevance
“…As we have shown in previous work, the reactivity of the terminal M(O) moiety is linearly correlated with O for [Ru(O)Co3O4(OAc)4(4-R-py)3] cubanes (R = OMe, H, CF3 and Me), 18 implying that this spin density (i.e., the oxyl character) can provide a useful measure in the design of C-H activation catalysts based on heterometallic cubanes. Natural bond orbital (NBO) analyses revealed a spin density of O = 0.36 in Ru(O)Co3O4 (Figure 3) and a significantly larger value of O = 0.93 in Fe(O)Co3O4 (Figure 3).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…As we have shown in previous work, the reactivity of the terminal M(O) moiety is linearly correlated with O for [Ru(O)Co3O4(OAc)4(4-R-py)3] cubanes (R = OMe, H, CF3 and Me), 18 implying that this spin density (i.e., the oxyl character) can provide a useful measure in the design of C-H activation catalysts based on heterometallic cubanes. Natural bond orbital (NBO) analyses revealed a spin density of O = 0.36 in Ru(O)Co3O4 (Figure 3) and a significantly larger value of O = 0.93 in Fe(O)Co3O4 (Figure 3).…”
Section: Resultssupporting
confidence: 73%
“…Nonetheless, the HAA TS remains 25.7 kcal mol -1 higher in energy than the Ru(O)Co3O4⋯C6H12 reactant complex. The significant height of this barrier is consistent with the ease of isolating and characterizing the Ru cubane 15,18 despite its oxyl character. Once the HAA step has been completed, however, the oxygen rebound step proceeds readily over a low barrier of only 5.2 kcal/mol, yielding the RuCo3O4⋯C6H11OH product, which lies 5.0 kcal/mol below the initial Ru(O)Co3O4⋯C6H12 reactant complex.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…To complete this arsenal, additional enzymatic strategies for electron transfer use bimetallic or polymetallic assemblies such as iron‐nickel [Fe−Ni] or iron‐iron [Fe−Fe] cores involved in hydrogenases, and iron‐sulfur [3Fe‐4S] and [4Fe‐4S] clusters found in ferredoxins. A recent example has shown that a H atom abstraction step performed by RuCo 3 O 4 oxo cubanes with oxyl radical ligands in the context of proton‐coupled electron transfer (PCET) reactivity is facilitated by metal‐metal cooperation in the multimetallic cluster [11] . Cooperative mechanisms are however not limited to metals, and the crystal structure of dihydromethanopterin reductase is a textbook example of this.…”
Section: Introductionmentioning
confidence: 99%
“…A recent example has shown that a H atom abstraction step performed by RuCo 3 O 4 oxo cubanes with oxyl radical ligands in the context of proton-coupled electron transfer (PCET) reactivity is facilitated by metal-metal cooperation in the multimetallic cluster. [11] Cooperative mechanisms are however not limited to metals, and the crystal structure of dihydromethanopterin reductase is a textbook example of this. This enzyme catalyzes the final step of methanopterin biosynthesis and is a 24-subunit cubic protein cage containing 48 molecules of FMN, which act as either cofactor or electron donor.…”
Section: Introductionmentioning
confidence: 99%